Ivan Pavlov's Behavioral Counseling Effectiveness with Modeling Techniques to Improve Character Associate with the opposite sex through Lesson Study - Agus Arya Sastrawan; Ketut Gading; I Ketut Dharsana (Universitas Pendidikan Ganesha)
This study is to study the effectiveness of Ivan Pavlov's modeling counseling in grade ten. The research is quasi-experimental design with pre-test, and post-test control group. A sample of 30 students with df 29. Methods of data collection using questionnaire's characters to help others as much as 30 items. The results of the data analysis are the value of tcount 3, 408 > ttable 1,67 so Ho rejected and Ha accepted. So there is a significant heterosexualty. It can be concluded that Ivan Pavlov's counseling is effective modeling to improve the characters mingle with the opposite sex.